Magnesium Protects Cognitive Functions and Synaptic Plasticity in Streptozotocin-Induced Sporadic Alzheimer’s Model - Xu, Zhi-Peng; Li, Li; Bao, Jian; Wang, Zhi-Hao; Zeng, Juan; Liu, En-Jie; Li, Xiao-Guang; Huang, Rong-Xi; Gao, Di; Li, Meng-Zhu; Zhang, Yao; Liu, Gong-Ping; et al. (PLOS ONE, 2014)
Alzheimer’s disease (AD) is characterized by profound synapse loss and impairments of learning and memory. Magnesium affects many biochemical mechanisms that are vital for neuronal properties and synaptic plasticity. Recent studies have demonstrated that the serum and brain magnesium levels are decreased in AD patients; however, the exact role of magnesium in AD pathogenesis remains unclear. Here, we found that the intraperitoneal administration of magnesium sulfate increased the brain magnesium levels and protected learning and memory capacities in streptozotocin-induced sporadic AD model rats. We also found that magnesium sulfate reversed impairments in long-term potentiation (LTP), dendritic abnormalities, and the impaired recruitment of synaptic proteins. Magnesium sulfate treatment also decreased tau hyperphosphorylation by increasing the inhibitory phosphorylation of GSK-3β at serine 9, thereby increasing the activity of Akt at Ser473 and PI3K at Tyr458/199, and improving insulin sensitivity. We conclude that magnesium treatment protects cognitive function and synaptic plasticity by inhibiting GSK-3β in sporadic AD model rats, which suggests a potential role for magnesium in AD therapy.